Freedom of movement of refugees: those forced to move find themselves without their human right to move - Slobe, Amanda Michele (AUC Knowledge Fountain, 2011)
For several decades, thousands of refugees have been fleeing into Kenya, and now Kenya is host to the world's largest refugee settlement. The mass influx of refugees and their protracted situation in Kenya gives evidence that there is a crisis within international refugee law. Refugees are a group of people that have been given a distinct rights regime, and their right to freedom of movement has been inhibited due to state practices. This is proof that the international refugee protection regime is at risk of breaking down. It is creating an environment in which states are resorting to harmful policies of containment and restrictions on movement. This is leading to the development of warehousing refugees which is considered a possible new solution to protracted refugee situations. This policy of containment is not a solution to the refugee â problem,â and the reality that it is considered a fourth solution among the three durable solutions raises concern. Warehousing is a consequence of the shortcomings of the 1951 Convention Relating to the Status of Refugees and subsequent 1967 Protocol which were not designed to respond to current protracted refugee situations. Regardless of the legality of warehousing under the refugee rights regime, it is a violation of the human right to freedom of movement. The lack of application of human rights law to refugees symbolizes the harmful gap that exists between these two international law regimes.